2012
DOI: 10.1021/jz301038b
|View full text |Cite
|
Sign up to set email alerts
|

A Reaction Accelerator: Mid-infrared Strong Field Dissociation Yields Mode-Selective Chemistry

Abstract: Mode-selective chemistry has been a dream of chemists since the advent of the laser in the 1970s. Despite intense effort, this goal has remained elusive due to efficient energy randomization in polyatomic molecules. Using ab initio molecular dynamics calculations, we show that the interaction of molecules with intense, ultrashort mid-infrared laser pulses can accelerate and promote reactions that are energetically and entropically disfavored, owing to efficient kinetic energy pumping into the corresponding vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…The results of molecular dynamics simulations of the dissociation ClCHO + with two laser pulses are listed in Table . In earlier work, we found that a single short, intense 7 μm laser pulse (90 fs, 0.09 au) perpendicular to the C–H bond successfully promoted the high energy channel for ClCHO + dissociating to HCl + + CO. Hence this wavelength and orientation can serve as reference for the various two pulse sequences in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of molecular dynamics simulations of the dissociation ClCHO + with two laser pulses are listed in Table . In earlier work, we found that a single short, intense 7 μm laser pulse (90 fs, 0.09 au) perpendicular to the C–H bond successfully promoted the high energy channel for ClCHO + dissociating to HCl + + CO. Hence this wavelength and orientation can serve as reference for the various two pulse sequences in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The simulations of dissociation were carried out by classical trajectory calculations on the ground state Born‐Oppenheimer surface for aligned formyl chloride cations in the time varying electric field of the laser pulses. As in our previous studies, the B3LYP/6‐311G(d,p) level of theory was chosen as a suitable compromise between accuracy of the potential energy surface and efficiency in the trajectory calculations. Molecular dynamics calculations were carried out with the development version of the Gaussian series of programs and the PCvelV integrator with a step size of 0.25 fs and Hessian updating for 20 steps before recalculation of the Hessian.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The interaction of the molecule with the laser field was calculated in the semiclassical dipole approximation. (1) μ⃗ is the dipole operator, E ⃗ (t) is the electric field component of the laser, and s⃗ (t) describes the shape of the pulse. The present study used a four-cycle linearly polarized trapezoid pulse (2) or a cosine squared pulse…”
Section: ■ Methodsmentioning
confidence: 99%
“…1,2 In the present work, we examine the isomerization and fragmentation of CH 3 NH 2 + , CH 3 OH + , and CH 3 F + by short intense 7 μm laser pulses. This work is motivated by recent studies of methanol cations by Yamanouchi and co-workers using pump−probe coincidence momentum imaging.…”
Section: ■ Introductionmentioning
confidence: 99%